2022
DOI: 10.1002/clt2.12200
|View full text |Cite
|
Sign up to set email alerts
|

The burden of chronic rhinosinusitis with nasal polyps and its relation to asthma in Finland

Abstract: Background Chronic rhinosinusitis with nasal polyps (CRSwNP) is commonly associated with asthma. Treatment of CRSwNP includes intranasal and systemic corticosteroids, with non‐responsive patients commonly considered for endoscopic sinus surgery (ESS). This nationwide register‐based study evaluated the incidence, prevalence, and treatment burden of CRSwNP in Finland, and their association with the presence and severity of comorbid asthma. Methods Electronic health records of patients diagnosed with CRSwNP betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Additionally, it was revealed that the relative proportion of pediatric and adult CRSwNP patients who underwent baseline ESS was 47% and 48%, respectively. In Finland, the reported nationwide average ESS rate is 0.71 per 1000 inhabitants, 39 and a recent study showed that among 18,600 CRSwNP patients in Finland, ESS was performed for 47% of the patients 40 . Therefore, our findings might reflect a comparable prevalence of ESS among CRS patients.…”
Section: Discussionsupporting
confidence: 47%
“…Additionally, it was revealed that the relative proportion of pediatric and adult CRSwNP patients who underwent baseline ESS was 47% and 48%, respectively. In Finland, the reported nationwide average ESS rate is 0.71 per 1000 inhabitants, 39 and a recent study showed that among 18,600 CRSwNP patients in Finland, ESS was performed for 47% of the patients 40 . Therefore, our findings might reflect a comparable prevalence of ESS among CRS patients.…”
Section: Discussionsupporting
confidence: 47%
“…33 Between 2012 and 2019 in Finland, the prevalence of CRSwNP rose from 602.2 to 856.7 patients per 100,000 people. 34 In this patient group, presence of severe asthma significantly increased the probability of receiving systemic corticosteroids and undergoing ESS. 34 A large hospital registry study in Finland 35 found that CRSwNP was associated with a disproportionate number of hospital visits (10/year, compared with 7 for asthma patients) despite comprising a relatively small proportion of the total number of diagnoses (7 patients at tertiary care per 100,000 inhabitants/year, vs 70 with asthma).…”
Section: Introductionmentioning
confidence: 82%
“…Taken together, these findings signal an urgent need for improved management of CRSwNP in Finland. 34 …”
Section: Introductionmentioning
confidence: 99%
“…Chronic rhinosinusitis (CRS) affects 7% to 27% of adults in European countries, 14% in the United States, and 2.1% to 8% in China 1,2 . CRS with nasal polyps (CRSwNP) is a heterogeneous, multifactorial disease with frequent recurrences despite medical and surgical interventions 3 . The underlying mechanisms that contribute to the persistent inflammation of CRSwNP are not completely defined.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 CRS with nasal polyps (CRSwNP) is a heterogeneous, multifactorial disease with frequent recurrences despite medical and surgical interventions. 3 The underlying mechanisms that contribute to the persistent inflammation of CRSwNP are not completely defined.…”
Section: Introductionmentioning
confidence: 99%